A Study of Indian Organizational Development at Present - Thakur, Satendra (Prabandhan: Indian Journal of Management, 2011)
Throughout the research paper, the researchers have discussed about organizational development at present in India. We also can say that now-a-days change has become very important for the success of any organization. Changes may arise from Government legislation or demographic factors such as age, society and workplace. In this article, it is also discussed that the development of any organization is based on understanding of behavioral science as it is concerned with how people and organizations function and how they can affect human functioning. The paper also discusses how an organization evolves through the various life cycles. For the success of any organization, intervention is required from time to time. The paper also gives directions, issues and challenges faced by the Indian organizations in the present times.